Position of Female Prisoners in India: A Critical Analysis (International Journal of Food and Nutritional Sciences, 2022)
The primary reason for this research paper is to highlight the issues of the female prisoners,looking behind the bars and disclose all of the rights that are protected for women in prison,as well as the reasons why women commit crimes. Indian culture gives a good status to thefemales. She contributes significantly to the society.